Use of roadmaps of evaluation to diagnose the financial viability of long-term investment alternatives - Montini, Mario José; Dos Santos, José Odálio (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
This research addresses the contribution of a standardized roadmap to qualify decision-making on the financial viability of long-term investment alternatives. For this, it uses a case study of a company that produces promotional videos for TV and Internet, reanalyzed by an international consulting firm. The main limitation for the reanalysis of the investment was the contracting company having restricted the scope of the work to an economic-financial evaluation study without providing information of competition, market research or commercial strategy. In this context, questionable internal data were taken into account such as assumptions, projections and arbitrated data. Consequently, if the reanalysis of the investment were both hinged upon the stages of the proposed evaluation roadmap and complemented by market strategy information, it would certainly contribute to reducing the risk of the investment.